PEMANFAATAN EKSTRAK DAUN SEMBUNG (Blumea balsamifera L) UNTUK PENGOBATAN PENYAKIT MOTIL AEROMONAS SEPTICAEMIA PADA IKAN LELE - Anis Zubaidah; Masitoh Masitoh; Hany Handajani (Universitas Sriwijaya, 2021)
Nga champora is one of the plants than can be antibacterial agent to treat Motile Aeromonas Septicemia (MAS) disease. Nga champora contain more than a hundred active compounds, but most of what is done for research is about flavonoids, alkaloids, steroids, tannin, glicosides and atsiri, which have bioactivity effects both in vivo and in vitro. The purpose of this study is to determine the effectiveness of MAS disease treatment using nga champora. The experimental method was used in this research using with five treatments, thai is: A (500 ppm), B (600 ppm), C (700 ppm), and Kontrol treatment. The results showed that the higher has the higher resistance to A. hydrophillawith a value of 5.7 mm (500 ppm) to 8.3 mm (700 ppm), and a life speed of up to 60% (700 ppm). Then it can be concluded that sembung leaf extract is effectively used as a cure for MAS disease Keywords: alternatif treatment, bacterial disease, immune respon, maseration